If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3m + 5) = 0 Reorder the terms: 2(5 + 3m) = 0 (5 * 2 + 3m * 2) = 0 (10 + 6m) = 0 Solving 10 + 6m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 6m = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 6m = 0 + -10 6m = 0 + -10 Combine like terms: 0 + -10 = -10 6m = -10 Divide each side by '6'. m = -1.666666667 Simplifying m = -1.666666667
| 3x+6=89-5x | | -27=x+19 | | -2(5-3m)= | | 3(7)/3= | | 3z-(10)=1 | | log(12x^4)-log(2x^3)=2 | | 4(5+7b)+6b=-252 | | cos(x)=-0.5 | | 5ln(x-11)-3=7 | | 8x^2-6x-3=0 | | 3(5-15)=m-5 | | 3x+25=12x+83 | | 3a-1(-1)=-5 | | 4(3y-3)-2y=-9 | | 4v+-3v-4=13 | | 6x^2-2x^3-4x=0 | | 2k-16-10k=-2k | | 207-7x=38x+22 | | -12-3+9= | | 6(x+4)-(2x-8)= | | 5-(-8)=x | | y^2-5y-3=0 | | 5(d-6)+6= | | 2m^3-5m^2-12m=0 | | (2x-3)+(x^2-4x)=180 | | 5x^2+3x-16=32-31x | | -3u+8=14 | | c-(-2)=68 | | 3y+4=-20 | | 56=4y | | 50=(x+10)x | | [(5*6-4)-20]= |